An in-depth multidimensional review of hypertension in adolescents in relation to obesity: Risk approach management is the solution - Fadl, Azza Abul-; Al-Jawaldeh, Ayoub (Indian Journal of Child Health, 2021)
Background: The emergence of isolated high blood pressure (HBP) among adolescents and its relation to obesity needs to be investigated. Aim: This study aims to assess prevalence, underlying risk factors, and consequences of HBP among adolescents in Egypt. Methods: We consolidated findings from three studies. The first one examined 150 adolescents (age: 16–18 years) for HBP and obesity using body mass index (BMI); the second one studied 150 adolescents for the lifestyle risk factors in relation to depression, anxiety, general health score, and suicidal score (SS) using relevant tools; the third one was a nested case–control study of 60 obese versus 60 non-obese adolescents examined for HBP, BMI, lifestyles and dietary habits, biochemical markers as lipid profile, fasting blood sugar (FBS), insulin, and homeostatic model assessment for insulin resistance (HOMA-IR). Results: In Stage I, the prevalence of HBP was 8% of whom, 58.3% were obese. Stage II: Dietary risk behavior as junk foods (high in salt) and soft drinks was 75.3% and 80%, respectively, and was linked with a high SS. Smoking was associated with a high anxiety score (p